2020
DOI: 10.1177/0363546520914942
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study of Radiographic Measures Predicting Failure of Arthroscopy in Borderline Hip Dysplasia: Beware of the Tönnis Angle

Abstract: Background: Hip arthroscopy has been previously demonstrated to be an effective treatment for adult mild hip dysplasia. There are many radiographic parameters used to classify hip dysplasia, but to date few studies have demonstrated which parameters are of most importance for predicting surgical outcomes. Purpose: To identify preoperative radiographic parameters that are associated with poor outcomes in the arthroscopic treatment of adult mild hip dysplasia. Study Design: Case-control study; Level of evidence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…This may be an issue with statistical power. However, a recent study by McQuivey et al 12 found an association between increased Tönnis angle and failure of hip arthroscopy in patients with borderline hip dysplasia. Interestingly, they found no association between failure rates and lower LCEA, lower anterior center-edge angle, extrusion index, or ADW.…”
Section: Discussionmentioning
confidence: 93%
“…This may be an issue with statistical power. However, a recent study by McQuivey et al 12 found an association between increased Tönnis angle and failure of hip arthroscopy in patients with borderline hip dysplasia. Interestingly, they found no association between failure rates and lower LCEA, lower anterior center-edge angle, extrusion index, or ADW.…”
Section: Discussionmentioning
confidence: 93%
“…34 The indications to proceed with revision hip preservation surgery were as follows: no evidence of severe cartilage damage on magnetic resonance imaging or arthrogram, no joint space narrowing, or an unbroken Shenton line. Furthermore, the relative indications to advance to isolated revision hip arthroscopy without a concomitant bony procedure (eg, PAO) were as follows: LCEA between 18° and 25°, Tönnis angle ≤10°, 40 or femoral anteversion <25°, as well as evidence of intra-articular sources of pain, such as residual cam-type morphology, labral retear, or capsular defect. 24 Relative indications for concomitant osteotomy and arthroscopy were bony deformity outside the measures cited, ligamentous laxity with Beighton score ≥4, and ligamentum teres tears indicating gross instability.…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria for this study were as follows: (1) insufficient or incomplete preoperative radiographs, (2) a history of surgery on the affected hip, (3) other intra-articular pathology (eg, evidence of slipped capital femoral epiphysis, true dysplasia [lateral center-edge angle of <18° or 18°-25° with increased Tönnis angle of >10°], 16 Legg-Calve-Perthes disease), or (4) symptomatic extra-articular impingement.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of an isolated labral or cartilage tear on magnetic resonance imaging scan without subjective hip pain or aforementioned clinical signs did not constitute an indication for hip arthroscopy given the previously documented high prevalence of asymptomatic labral tears. 12 Exclusion criteria for this study were as follows: (1) insufficient or incomplete preoperative radiographs, (2) a history of surgery on the affected hip, (3) other intraarticular pathology (eg, evidence of slipped capital femoral epiphysis, true dysplasia [lateral center-edge angle of \18°o r 18°-25°with increased Tönnis angle of .10°], 16 Legg-Calve-Perthes disease), or (4) symptomatic extra-articular impingement.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%